Philippine Social Security System: An Evaluation Of Strategic Approach To Digital Services - Galang, Glenn Mhar B.; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
ABSTRACT This study was conducted to assess the digital services of the Philippine Social Security System in terms of processing of personal data, organizational measures, physical measures, and technical measures. The research employed a descriptive-correlational approach, utilizing a questionnaire as the primary data gathering instrument. However, interviews among the 5 heads of the 5 biggest branches of SSS in the NCR were utilized to validate the data taken in the questionnaire among the 3 groups of respondents: BPOs (120), front-liners (180), and clients (1292). For BPOs and front-liners, complete enumeration was used, while convenience sampling was utilized for clients. Weighted mean and one-way ANOVA were used for the treatment of the data. The study revealed that all the indicators in all four variables were, on average, partially implemented. The seriousness of the encountered problems led to a highly recommended assessment of the presented solutions. Further investigation revealed no significant differences in assessment among the three groups of respondents. The study's findings led to the conclusion that Philippine Social Security requires additional physical and electronic paperwork. Additionally, the Philippine Social Security System shares and exchanges personal data with other parties through digital channels. Furthermore, the corporate orientation course for newly hired or absorbed employees does not include security management, despite its availability. Finally, SSS has yet to use advanced technology to detect fake, altered, and fraudulent documents; hence, it still needs to use advanced technology to formulate a comprehensive data security manual to integrate digital measures against cybercrime. Therefore, the study's findings and conclusions inform the following recommendations: Firstly, we should archive and retain physical or electronic documents containing personal data in secure and protected record rooms, offsite storage facilities, or receptacles or cabinets, in accordance with the issued policies. Second, only with prior consent or authority from the data subjects, a judicial order, or a data sharing agreement can we use digital platforms to disclose and share personal data with third parties. Third, newly hired or absorbed employees should include data security management in their corporate orientation course. Fourth, we should use advanced technology to detect fake, altered, and fraudulent documents. Finally, we should formulate a data security manual to incorporate digital measures against cybercrime.